The Semantics of Mukhtāl and Fakhūr in the Qur’an: Perspectives from Indonesian Tafsir Scholarship - Azkia, Farhani; Azizy, Jauhar; Nasution, Fauziah; Almuntarizi (Jurnal Ilmiah Al-Mu'ashirah: Media Kajian Al-Qur'an dan Al-Hadits Multi Perspektif, 2026)
This study addresses a gap in Qur’anic semantic studies regarding the relational meanings mof the terms mukhtāl and fakhūr, which are often treated as interchangeable synonyms of arrogance. Previous studies tend to focus on individual verses or on a single term, leaving the semantic interaction embedded in the phrase mukhtālan fakhūran underexplored. This study employs a qualitative method combining linguistic analysis (covering morphology, forms of hyperbole (ṣīghah mubālaghah), and syntagmatic relations) and empirical data obtained from interviews with Indonesian Quranic scholars. The results reveal that mukhtāl primarily denotes embodied or performative arrogance manifested in actions, while fakhūr signifies verbal and discursive arrogance expressed through self-glorifying speech. The phrase mukhtālan fakhūran thus represents a complementary semantic unit rather than a redundant expression. This distinction is further contextualized through contemporary social phenomena such as digital narcissism and flexing, where verbal exhibitionism and performative self-display intensify classical forms of arrogance. The study contributes both theoretically, by refining Qur’anic semantic analysis of near-synonyms, and practically, by offering an ethical framework for understanding modern social behavior.